Determination of enhancement in D-region electron density using solar flare model and GOES- 7 measurements - Mardina Abdullah,; Ahmad Faizal Mohd Zain, (2005)
This investigation elucidates the enhancement of production of electrons in the ionospheric D region by soft solar X-ray flares. A simple solar X-ray flare model is established for the purpose of this study. The in-step variation of calculated enhanced electron densities with measured values of enhanced flux intensities obtained by the GOES7 X-ray detector is understood quantitatively by the difference of arrival time of the maximum enhanced electron density with the arrival time maximum enhanced flux intensity i.e., the arrival time lag. This is compared with time lag taken from the X-ray flare model under the condition that the enhanced the electron densities are much smaller than electron density in a quiet state. The comparison of theoretical time lag or the response rate shows a good agreement with that obtained by measurements. By using this model, physical quantities such as the decreasing slope coefficient of flare model b( , z) are described in detail to identify their effects to enhanced electron densities. Good or poor in-step variation of enhanced electron densities to enhanced flux intensities through their increasing, maximum and decreasing stage is mostly dependent on fundamental physical quantities b( , z), by evaluation of the response rate. Time lag, which is inversely proportional to b( , z), shows good response. The temporal variation of b( , z) is also studied. This result can also be applied to disturbance phenomena that have a similar form